Integrated Approach to Company Strategic Analysis Using Modern Methods - Braun, David; Taušer, Josef; Joska, Jan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The Master Thesis deals with strategic analysis using modern methods. These methods are then applied in the form of a case study focusing on Hewlett Packard Enterprise. Thus, the aim is to use the case study to analyse the competitive industry of the company mentioned above. For this reason, in the theoretical part, I focused on explaining the methods and selected trends in the information technology market. In the practical part, I applied the theory to the researched company. With the help of qualitative and quantitative methods, internal and external analysis, I identified the strengths and weaknesses of Hewlett Packard Enterprise. Finally, I conclude with a summary of the Master Thesis results and recommendations for future research.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses